IMPLEMENTASI BEST PRACTICE DALAM PERENCANAAN DAN PELAKSANAAN PEMBELAJARAN MAHASISWA PPL UNIVERSITAS PGRI SUMENEP DI SMK NEGERI 1 KALIANGET - Arifatul Aini; Zainul Muqit; Halimatur Rafiqah; Putri Ayu Andini; Dwi Risma Siti Aisyah; Feri Nanda Setiawan; Ilham Budi Wicaksono; Rendra Kusuma (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the implementation of best practice in planning and implementing learning by students of the Teaching Practice Program at Universitas PGRI Sumenep in SMK Negeri 1 Kalianget using a desciptive qualitative approach. The research subjects consisted of seven PPL students, and the data were collected through observation, documentation, and reflection, then analyzed descriptvely. The results show that learning planning was systematically designed based on the Merdeka Curriculum and deep learning principles, while the implementation of learning was active and student-centered through the use of varied methodsand digital-based learning media. In practice, students faced severall challenges, including differences in student characteristics, classroom management, and limitationsin digital media. These challenges were addressed through adaptive strategies such as method variation, individual approaches, and continuousreflection. Therefore, the implementation of best practice in the PPL program contributes to improving pedagogical competence and the professional readiness of prospective teachers.